2016
DOI: 10.5005/jp-journals-10005-1331
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dermatoglyphic Peculiarities with Dental Caries in Preschool Children of Lucknow, India

Abstract: Background: Dermatoglyphics refers to study of the intricate dermal ridge configurations on the skin covering the palmar and plantar surfaces of hand and feet. The basis of considering dermatoglyphic patterns as genetic marker for dental caries is that the epithelium of finger buds as well as enamel has ectodermal origin, and both develop at the same time of intrauterine life.Aim: To assess the relationship between fingerprint patterns and dental caries among preschool children of Lucknow city.Study design: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 11 publications
2
17
0
Order By: Relevance
“…Dexterity also plays an important role in dental caries as authors in their previous studies reported that subjects who used their right hands were doing better in terms of oral hygiene than those using the left with lower prevalence of caries. [10] Along with that it was also stated in previous studies [1,7,8,9] that irrespective of dexterity, the subjects with whorl pattern showed high caries prevalence.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Dexterity also plays an important role in dental caries as authors in their previous studies reported that subjects who used their right hands were doing better in terms of oral hygiene than those using the left with lower prevalence of caries. [10] Along with that it was also stated in previous studies [1,7,8,9] that irrespective of dexterity, the subjects with whorl pattern showed high caries prevalence.…”
Section: Introductionsupporting
confidence: 64%
“…Authors have proved in their studies [1,7,8,9] that subjects with whorl pattern showed high caries incidence. Dexterity also plays an important role in dental caries as authors in their previous studies reported that subjects who used their right hands were doing better in terms of oral hygiene than those using the left with lower prevalence of caries.…”
Section: Introductionmentioning
confidence: 99%
“…But, in the present study, group I (CP caries-active group) is comprised of two genetic factors, namely CP and susceptibility to caries. In CP, an increase in arches has been reported by Simsek et al 21 and Bhat et al 22 The second genetic factor which is susceptibility to caries has also been reported to be associated with a decrease in frequency of arches by Singh et al 19 and Chinmaya et al 4 They have observed a negative correlation of arches with dental caries. This cumulative effect might be the reason for the presence of more number of arches in group I (CP caries-active group) than in group II (healthy caries-active children).…”
Section: Discussionmentioning
confidence: 89%
“…Case history was recorded using “Dentition status and treatment needs,” (WHO basic oral health assessment form 1997). 6 Dental caries was recorded using the DMFT and deft index for permanent and primary teeth using type 3 examination. Intraoral examination of the children with CP was carried out in the presence of their school teacher or the care giver, so as to gain cooperation from the children.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, there was no significant relationship between the loop pattern of fingerprints and higher incidence which was similar to the results of the study by Madhusudan et al [9] And also, whorls and loops were almost equally found in those with a lower incidence of caries. This was, however, contradicting the studies by Navit et al [10] concluding that whorls predict lower incidence of caries and also studies by Anitha et al ,[11] Sanghani eta l.,[1] Abhilash et al ,[12] and Singh et al [13] stating that whorls are more prevalent in caries active children. The reason for this difference in results may be because of the different classifications used to analyze the fingerprints and may also be due to the higher number of participants that were considered during their studies.…”
Section: Discussionmentioning
confidence: 99%